REDUCING THE PHENOL IN AL-NAJAF PETROLEUM REFINERY WASTEWATER BY USING ELECTROOXIDATION TECHNIQUE (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
Industrial effluents, hazardous biological waste, and wastewater from crude oil refining all contribute to water contamination. All of these pollutants are emitted into the environment and have emerged as a modern issue owing to their hazardous organic and inorganic constituents. This research aimed to decrease the concentration of organic phenol (C₆H₅OH), a contaminant found in the wastewater from the Najaf refineries in Iraq. Laboratory research used electrical approaches, including electro-oxidation (EO), which has shown significant efficacy in eliminating dissolved phenol. Graphite electrodes served as the anode in the electrolytic cell, while steel (SS) electrodes functioned as the cathode inside a tough plastic casing. The starting phenol content in the treated water was 50 ppm under the following parameters: electric current density (10, 15, 20) mA/cm2, sodium chloride (NaCl) concentration (0, 1.5, 3) g/L, acidity (pH) (3, 7, 10), and duration (2–4 h). The results showed that the higher the current density and NaCl concentration, the better the removal rate in both strong and moderate acidity, with the best conditions for removal being a current density of 15 mA/cm², a pH of 3, a NaCl concentration of 3 g/L, and a duration of 3 hours. A removal rate of 96.3% was attained under the specified circumstances.